PENGELOLAAN OBJEK WISATA PADA TAMAN MARGA SATWA DAN BUDAYA KINANTAN KOTA BUKITTINGGI - Abdul Mu’ Arif; Mimin Sundari Nasution (Cross-border, 2023)
Management is an activity that is carried out in achieving organizational goals in which there is a process of formulating goals and setting goals and supervision in order to achieve organizational goals. The English term for management is Management. The Kota Bukittinggi Animal and Cultural Park is a tourist attraction that is one of the historical landmarks in Kota Bukittinggi, as it was built during the Dutch colonial period. The purpose of this study is to know the management of the Kinantan Animal and Cultural Park tourist attractions (TMSBK) and to know the inhibitory factors in their management. The study used the theory according to Georger R. Terry used four indicators, namely Planning, Organization, Implementation, Supervision. The Research Methods used in this study used descriptive qualitative methods and techniques for collecting data through primary and secondary data sources obtained through observation or observation processes, interviews and documentation by researchers and then being analyzed. The research shows that the management of Taman Marga Animal and Cultural attractions in Kota Bukittinggi has been carried out based on their plans, but there are several problems in their management such as lack of infrastructure related to the procurement of animal cages caused by budget factors and the placement of human resources that doesn't fit his competence.